Mediating Effect of Entrepreneurial Skills on the Relationship between Entrepreneurial Orientation and Entrepreneurial Intention - Ibrahim, Najafi Auwalu; Muhammad, Ibrahim Garba; Muazu, Muazu Hassan (UUM Press, 2017)
The uncertainty nature of today’s environment and the increase in unemployment across the globe necessitate the need to improve entrepreneurial activities among graduates. Although, prior studies have documented empirical support of entrepreneurial orientation to entrepreneurial intention, the role of entrepreneurial skills has not been fully documented. Also, the effect of entrepreneurial orientation differs with individual cultures. Hence, the study examined the mediating role of entrepreneurial skills on the relationship between entrepreneurial orientation and entrepreneurial intention using a sample of 143 Nigerian students. This study used a quantitative research approach, while the Partial Least Square Equation Modelling (PLS-SEM) was used for data analysis. The findings of the study revealed that both entrepreneurial orientation and entrepreneurial skills have positive relationships with entrepreneurial orientation. In addition, entrepreneurial skills mediate the relationships between entrepreneurial orientation and entrepreneurial intention. The findings of this study reinforce the assumption that EO shapes the activities of entrepreneurs, while their ES, in terms of negotiating, opportunity recognition and networking ability increases on a daily basis which will lead to entrepreneurial success.